Implementasi Model Pembelajaran Interaksi Sosial Untuk Meningkatkan Karakter Peserta Didik - Koko adya winata; Aan Hasanah (Universitas Pendidikan Muhammadiyah Sorong, 2021)
Abstrak:This paper aims to examine the application of social interaction learning models to improve the character of students. Social interaction model is a learning model that holds that the learning process is inseparable from the reality of life. Students are understood with the phenomena that exist in life, so the learning process is intended to prepare students to be able to interact widely in the community. In this case, students are taught about how to interact politely, harmoniously, democratically and uphold the values ​​of civilization called character. The research method used is descriptive qualitative. By using a qualitative approach researchers are expected to be more flexible in understanding, observing and conducting more accurate reviews regarding the application of social interaction learning models to improve the character of students. The findings in this study can be concluded as follows: a) learning model of social interaction can improve the character of students manifested in social interaction better, b) the ability of students to interpret phenomena in society critically and politely, c) foster motivation intrinsic learners to character values. Kata Kunci: Model Penerapan Pembelajaran, Model Interaksi Sosial, Karakter Mahasiswa.